English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Need homework help:

lim(x->1) (1-x)/sqrt(12-3x)-3

lim(x->1) (x^3-1)/(x-1)

lim(x->0) (1-cosx)/(1+sinx)

lim (x->0) (1-cosx)/(sinx)

Don't have to do all of them, just please show me your steps.

2007-07-15 12:28:14 · 4 answers · asked by Anonymous 1 in Science & Mathematics Mathematics

4 answers

One trick to doing limits of functions, is to separate your function into chunks where limits are easy to find.

e.g., the first one

Lim(x->1) [ (1-x)/SQRT(12-3x) - 3]
=
Lim (1-x) / Lim(SQRT(12-3x)) - Lim(3)

Lim(3) = 3 whatever x does.

Lim(1-x) = 0 as x approaches 1.

Lim(SQRT(12-3x)) = SQRT(9) as x approaches 1.

Replacing, we have
Lim(x->1) [ (1-x)/SQRT(12-3x) - 3]
=
0 / 9 - 3 = -3

(Depending where the "-3" belongs)

The second one may be a bit of a problem:
lim(x->1) (x^3-1)/(x-1)
If we try directly, we get
lim(x^3-1) = 0 and
lim(x-1) = 0
0/0 = indeterminate.

However, we can split it differently:

(x^3-1) = (x-1)(x^2+x+1)

Therefore:
lim(x->1) (x^3-1)/(x-1) =
lim(x^2+x+1)*lim[(x-1)/(x-1)] =
lim(x^2+x+1)*lim(1)

lim(x^2+x+1) = 3 as x approaches 1
lim(1) = 1 whatever x does.
3*1 = 3

This is NOT the same as saying that the original function is equal to 3 when x = 1 (after all, the original function continues to have a division by zero at that position). However, it can be completed by giving it the value of the limit at x=1.

2007-07-15 12:45:55 · answer #1 · answered by Raymond 7 · 1 0

I'll do two. You do the others, but let me know if you need help.

lim(x->1) (x^3-1)/(x-1)
Plug in 1 and you get 0/0, an indeterminate form. So you have to simplify:
Difference of cubes for numerator:
lim(x->1) [(x-1)(x^2 + x + 1)]/(x-1)
lim(x->1) (x^2 + x + 1)
= 1^2 + 1 + 1 = 3

lim(x->0) (1-cosx)/(1+sinx)
You can just plug in for this one:
= [1 - cos(0)] / [1 + sin(0)]
= [1 - 1] / [1 + 0]
= 0

2007-07-15 12:40:39 · answer #2 · answered by whitesox09 7 · 0 0

lim(x->1) (1-x)/sqrt(12-3x)-3
= lim x->1 (1-x) [sqrt(12-3x) +3]/ [sqrt(12-3x)-3 ] [sqrt(12-3x) +3]
= lim x->1 (1-x) [sqrt(12-3x) +3]/ [ 12-3x-9]
= lim x->1 (1-x) [sqrt(12-3x) +3]/ [ 3-3x]
= lim x->1 (1-x) [sqrt(12-3x) +3]/ 3[ 1-x]
= lim x->1 [sqrt(12-3x) +3]/ 3
= [sqrt(9) +3]/3 = 2


lim(x->1) (x^3-1)/(x-1)
= lim x->1 (x-1)(x^2 +x +1)/ (x-1)
= lim x->1 x^2 +x +1 = 3

2007-07-19 16:02:04 · answer #3 · answered by robert 6 · 0 0

maybe some people just right silly things for an answer just to get 2 points and if you are a serious yahoo Q and A then you will not give up trying to achieve the next level....often unserious people (like tryping something really out just for the sake of the points...maybe even one letter) gets disheartenned easily and would give up if it is not easy to get to the unlimited number.......dont give up i am sure u will get there

2016-05-18 21:17:33 · answer #4 · answered by Anonymous · 0 0

fedest.com, questions and answers